Styles of continental rifting: crust-mantle detachment and mantle plumes - Zeyen, Hermann; Volker, Frank; Wehrle, Veronika; Fuchs, Karl; Sobolev, Stephan V.; Altherr, Rainer (Tectonophysics, 1997)
Observations made in different continental rift systems (European, Red Sea-Gulf of Aden, and East African Rift Systems) were investigated in terms of the influence of different parameters on the style of rifting. Apart from the lithospheric thermal regime at the time of rift initiation, the process of rifting seems to be mainly controlled by the far-field stress regime and the presence or absence of a mantle plume. In a hot lithosphere the low viscosity of the lower crust enables the upper crust to be detached from the mantle and be deformed independently under far-field stresses. Therefore, in western Europe the main rifts could open obliquely to the direction of mantle movement in crustal levels without appreciable extension in the lithospheric mantle. In contrast, the colder lithosphere of Arabia did not allow detachment of crust and mantle. Therefore, despite being in a similar tectonic situation as in western Europe, i.e. rifting in front of an orogen, the whole lithosphere deformed congruently. Rift opening occurred parallel to mantle movement, i.e. parallel to the direction of extensional stress in the lithospheric mantle induced by the pull of the subducting slab at the orogenic front. The forces needed to extend the whole relatively cool Arabian lithosphere could, however, not be produced by slab pull alone. Additional forces and weakening of the lithosphere were produced by the Afar mantle plume. Mantle plumes are generally not able to break very thick cratonic lithosphere but they deflect sidewards when hitting this kind of lithosphere. Warmer (but still relatively cool) lithosphere like in the surroundings of the East African Tanzania craton or in Arabia can, by the buoyancy of a plume, be bent strongly enough to break. As a consequence, long linear rift structures develop with generally high shoulders. The presence of a plume explains thus the position of the East African and Red Sea-Gulf of Aden rifts. Under far-field compression, rifts will open only a small amount, whereas under far-field extension continental break-up may occur. A plume hitting a hot lithosphere may penetrate it without producing long linear rifts. Instead, crustal deformation will be distributed in parallel basins over a wide area with only minor amounts of rift shoulder uplift as has happened in northern Kenya and the French Massif Central.